Methyl cellulose bridging between alumina surfaces - Yılmaz, Hüseyin; Sato, Kimiyasu; Sato, Katsuya; Hotta, Yuji; Watari, Koji (Ceramic Soc Japan-Nippon Seramikkusu Kyokai, 2010)
Forces between alpha-alumina surfaces in NH4+ salt of poly(acrylic acid) (NH4-PAA) and methyl cellulose polymer solutions at pH 9 were measured by colloid probe technique. The effect of water soluble methyl cellulose, with and without the presence of surfactant (NH4-PAA), on the surface forces was probed to understand the binding action of methyl cellulose between particles. Two types of cantilevers were used to probe the surface forces in the presence of adsorbed polymers at various concentrations. Strong polymer concentration dependence of surface forces was found. At high polymer concentrations due to the high coverage of surfaces, repulsive forces dominated the interaction. Methyl cellulose bridges have been measured up to similar to 300 nm. The pretreatment of surfaces with NH4-PAA resulted in much lower number of bridging events on retraction. (C) 2010 The Ceramic Society of Japan All rights reserved
Keywords: AFM; Colloid probe technique; Alumina; NH4-PAA; Methyl cellulose; Bridging